Enhanced glucose detection using dendrimer encapsulated gold nanoparticles benefiting from their zwitterionic surface. Issue 18 (12th December 2018) - Wang, Longgang; Zhu, Linlin; Yu, Qingyu; Chen, Shengfu; Cui, Yanshuai; Sun, Haotian; Gao, Dawei; Lan, Xifa; Yang, Qinghua; Xiao, Haiyan
Abstract: The application of ultrasmall gold nanoparticles as enzyme mimics has been drawing great attention. Herein, we developed zwitterionic dendrimer encapsulated gold nanoparticles (Au-G5MC NPs) for highly sensitive and simple colorimetric detection of glucose. Au-G5MC NPs showed peroxidase-like property, which could efficiently catalyze oxidation of 3, 3', 5, 5'-tetramethylbenzidine (TMB) in the presence of H2 O2, producing a blue color product (oxTMB). This peroxidase-like reaction follows a typical Michaelis-Menten kinetics. The Km towards TMB exhibited a lower value (0.194 mM) than that of horseradish peroxidase (HRP, 0.434 mM). Furthermore, the peroxidase-like properties of Au-G5MC NPs enable colorimetric detection of the concentration of glucose with high selectivity. The linear concentration range of this method was from 14 μM to 166 μM with the detection limit down to 3.8 μM. More importantly, the detection was not interfered by proteins due to the single zwitterionic layer on the Au-G5MC NPs surface. These excellent properties are attributed to the ultrasmall size of gold nanoparticles and high stability of Au-G5MC NPs in complex medium. This catalytic system might have great potential applications for glucose detection in medical diagnostics and biochemistry in the future.